Fluffy$1 (Bs Thanksgivings - McMullan, Kate.; Smith, Mavis (New York : Scholastic, 1997)
After starring as an ear of corn in his school$1 (Bs Thanksgiving play, the classroom guinea pig enjoys his holiday at Maxwell$1 (Bs home, where he scares Grammy and battles a monster.s
"Cartwheel books."
Keywords: Guinea pigs -- Fiction; Thanksgiving Day -- Fiction; Schools -- Fiction